Design and Construction of An Optomechanical Coupler For Quantum Optical Experiments - Abbas, Hayat (2023)
Hybrid quantum systems have received significant interest, especially with the goal of technological exploitation of complementary capabilities for quantum information processing and communication tasks. Quantum transducers can be used to couple the properties of one object or system to different properties of another system, thus combining, for example, the robust transmission of photonic quantum states with strong interactions between material quantum objects. In a room-temperature environment, a spin-polarized atomic ensemble and a micromechanical oscillator over a one-meter distance are coupled to a free-space laser beam. This experiment requires a stable interferometer, which is usually done actively. Stabilizing a large path separation interferometer is cumbersome. Thus, we investigate an alternative way to build a robust polarization interferometer characterised by its stability with no requirement for any adjustment. This thesis constructs a hybrid quantum system consisting of a quantum transducer that maps small position changes of a micro-mechanical membrane onto the polarization of a laser beam. This is done with an interferometric setup that has reduced the need for stabilization. Specifically, an oscillating silicon nitride membrane placed in the middle of an asymmetric optical cavity causes phase shifts in the reflected, near-resonant light field. A beam displacer is used to combine the signal beam with a mode-matched, orthogonally polarized reference beam for polarization encoding. Subsequent balanced homodyne measurement is used to detect thermal membrane noise. The high signal-to-noise ratio should allow for detecting motional quantum noise in the regime of high optomechanical coupling strength. This setup can provide a robust quantum link between a micro-mechanical oscillator and other systems such as atomic ensembles.